1994
DOI: 10.1111/j.1748-0361.1994.tb00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Local Factors Affecting the Tendency to Bypass Local Hospitals for Inpatient Mental Health Care: An Exploratory Analysis

Abstract: Using the records of 2,171 rural residents of Illinois who received inpatient treatment for mental illness or substance abuse, this paper examines factors that influence the tendency to seek service from a distant rather than a local hospital. Results indicate that the age and insurance coverage of the individual, the per capita income of the community area, surrogates for the service orientation of the local hospital and the proximity of the patient's residence to an urban center are significant influences. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…Additionally, this study provides the first estimates of dentist bypass rates in the US. Empirical studies of hospital bypass in the United States have found rates of approximately 30 percent (17,18), with higher rates for specialty services such as surgical care (19) and inpatient mental health services (20). Overall, the rate of dentist bypass among our entire study population was 76.8 percent.…”
Section: Discussionmentioning
confidence: 77%
“…Additionally, this study provides the first estimates of dentist bypass rates in the US. Empirical studies of hospital bypass in the United States have found rates of approximately 30 percent (17,18), with higher rates for specialty services such as surgical care (19) and inpatient mental health services (20). Overall, the rate of dentist bypass among our entire study population was 76.8 percent.…”
Section: Discussionmentioning
confidence: 77%
“…1,2,[4][5][6][7][8][9][10][11] Patients covered by either commercial or managed care insurers have higher bypass rates than patients covered by other types of payers. 12 The elderly bypass local care less frequently, 1,2,4,10,11,13,14 and working men do so more frequently.…”
Section: By Pa S Sing Lo C a L Pr Im A Ry C A R Ementioning
confidence: 99%
“…Consumers' perceptions of the availability of local family physicians were also associated with migration for family physician care Individuals who perceived that a shortage of family physicians existed in their home county were more than twice as likely to choose family doctors in external market areas. This was expected as previous research has shown that the availability of local inpatient services is negatively related to migration for hospital care (Adams, et al, 1991;Goldsteen, et al, 1994;Williamson, et al, 1994). In further support of these findings regarding physician availability, when directly asked if and why they migrated for urzy type of health care, the main reason cited was that the service needed was not locally available Of course, conclusions based on consumers' perceptions of physician supply rest on the assumption that consumers can provide valid and reliable ratings of physician availability.…”
Section: Discussionmentioning
confidence: 59%
“…Unfortunately, although several studies have investigated migration for hospital care (Adams and Wright, 1991;Buwko, 1992Buwko, , 1994Goldsteen, et al, 1994;Williamson, et d., 1994), few have investigated migration for physician care. One notable exception is a study by Meinman and Makuc (1983) who found that approxi-A primary economic benefit to having physicians 1 c~ ' mately 47 percent of individuals living in a rural county adjacent to a metropolitan county and 45 percent living in a rural county nonadjacent to a metropolitan area migrated for physician services.…”
mentioning
confidence: 99%